2005
DOI: 10.2460/javma.2005.227.105
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative survival rates after surgery for diaphragmatic hernia in dogs and cats: 92 cases (1990–2002)

Abstract: Results in 68 dogs and cats that underwent surgery within 24 hours of admission suggested that early surgical intervention for acute diaphragmatic hernia was associated with good perioperative survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
2
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 2 publications
0
60
2
10
Order By: Relevance
“…The anatomical position of the organ and the location of the disruption often determine the herniated organs in diaphragmatic hernia. In several studies, including our current study, the liver has been found the most commonly herniated organ followed by the small intestine, stomach, omentum, spleen, pancreas, and large intestine (Schmiedt et al 2003;Hyun 2004;Gibson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical position of the organ and the location of the disruption often determine the herniated organs in diaphragmatic hernia. In several studies, including our current study, the liver has been found the most commonly herniated organ followed by the small intestine, stomach, omentum, spleen, pancreas, and large intestine (Schmiedt et al 2003;Hyun 2004;Gibson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Liver was the most frequently herniated organ and this was followed by small intestines, stomach, omentum, spleen, pancreas and large intestines (3,5,10,17).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of diaphragmatic line and cardiac silhouette, appearance of the abdominal organs, intestinal loops or gas in the thorax or thin abdomen are characteristic radiographic signs (5,8,12). Almost all abdominal structures have been reported to protrude into the thoracic cavity; liver, stomach, small intestines, spleen, omentum, pancreas are the commonly herniated organs but on rare occasion the kidney have been reported to be in the herniated organs (3,6,8,10,14). Perioperative mortality rates ranging from 8-18% have been reported in the researches (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…Cliniquement, le symptôme rapporté le plus fréquem-ment est une dysfonction respiratoire souvent traduite par une dyspnée, présente dans 72,4 % des cas aigus [5] ainsi que dans les cas chroniques associée alors à des vomissements et d'autres symptômes peu spécifiques (anorexie, abattement, perte de poids) [15]. De nombreux cas sont asymptomatiques suite au traumatisme.…”
Section: Spécificités Des Hernies Diaphragmatiques Chroniquesunclassified
“…Un contrôle radiographique du thorax doit donc être systématique après tout traumatisme important [1][2][3]. L'examen radiographique est également obligatoire dans le cas de hernie diaphragmatique chronique mais ne permet l'établissement d'un diagnostic que dans 66 % des cas [5] et nécessite d'être associé à d'autres examens d'imagerie (échographie ou radiographie avec produit de contraste, par exemple).…”
Section: Spécificités Des Hernies Diaphragmatiques Chroniquesunclassified